JUnit in action - Tahchiev, Petar; Massol, Vincent (Manning Pub., 2011)
"JUnit in Action, Second Edition is an up-to-date guide to unit testing Java applications (including Java EE applications) using the JUnit framework and its extensions. This book provides techniques for solving real-world problems such as testing AJAX applications, using mocks to achieve testing isolation, in-container testing for Java EE and database applications, and test automation. Written to help readers exploit JUnit 4.5, the book covers recent innovations such as the new annotations that simplify test writing, improved exception handling, and the new assertion methods. You'll also discover how to use JUnit extensions to test new application styles and frameworks including Ajax, OSGi, and HTML-based presentation layers. Using a sample-driven approach, various unit testing strategies are covered, such as how to unit test EJBs, database applications, and web applications. Also addressed are testing strategies using freely available open source frameworks and tools, and how to unit test in isolation with Mock Objects. The book will also bring you up to speed on the latest thinking in TDD, BDD, Continuous Integration, and other practices related to unit testing"--Resource description page.